Exploring disease-related and treatment-related issues and concerns experienced by adults with spondyloarthritis, inflammatory bowel disease and psoriasis to identify unmet needs: a qualitative clinical concept mapping study - Lene Dreyer; Lars Erik Kristensen; Mark Andrew Ainsworth; Tanja Schjødt Jørgensen; Simon Francis Thomsen; Katrine Risager Christensen; Marie Skougaard; Zara R Stisen; Rebekka Lund Hansen; Mette Mogensen (BMJ Open)
Objectives Exploring patients’ perspectives for significant factors of relevance in living with a chronic disease is important to discover unmet needs and challenges. The primary objective of this study was to explore disease-related and treatment-related issues and concerns experienced by adults with spondyloarthropathies (SpA) and associated diseases. As a secondary objective, we wanted to explore whether these factors were generic or disease dependent.Design We used group concept mapping (GCM), a validated qualitative method, to identify disease-related and treatment-related issues and concerns. Participants generated statements in the GCM workshops and organised them into clusters to develop concepts. Furthermore, participants rated each statement for importance from 1: ‘not important at all’ to 5: ‘of great importance’.Setting Participants were recruited during routine care at the outpatient clinic at the hospitals in the period from May 2018 to July 2022.Participants Eligible participants were adults ≥18 years and diagnosed with axial spondyloarthritis (AxSpA), psoriatic arthritis (PsA), psoriasis (PsO) or inflammatory bowel disease —split into Crohn’s disease (CD) and ulcerative colitis (UC).Results 52 patients participated in the 11 workshops divided into groups according to their diagnosis. They created a total of 1275 statements that generated 10 AxSpA concepts, 7 PsA concepts, 7 PsO concepts, 10 CD concepts and 11 UC concepts. The highest rated concepts within each disease group were: AxSpA, ‘lack of understanding/to be heard and seen by healthcare professionals’ (mean rating 4.0); PsA, ‘medication (effects and side effects)’ (mean rating 3.8); PsO, ‘social and psychological problems, the shame’ (mean rating 4.0); CD, ‘positive attitudes’ (mean rating 4.3) and UC; ‘take responsibility and control over your life’ (mean rating 4.0).Conclusion People with SpA and associated diseases largely agree on which concepts describe their disease-related and treatment-related issues and concerns with a few of them being more disease-specific.